Image Perception and Marketing Mix Affecting Tourist Revisit Behavior in Cultural Tourism Destinations in Suphan Buri Province - Sintam, Romklao (Journal of Cultural Approach, 2023)
The objectives of this research were to study 1) the relationship between image perception, marketing mix, and tourist revisit behavior, and 2) image perception and marketing mix effect on tourist revisit behavior in cultural tourism destinations in Suphan Buri Province. The sample consisted of 400 tourists in Suphan Buri Province and used quota sampling. A questionnaire was used as the data collection instrument. The descriptive statistics for data analysis consisted of frequency, percentage, mean and standard deviation. The hypothesis testing included Pearson’s correlation coefficients and multiple regression analysis. The results revealed that image perception was significantly related to tourist revisit behavior at a level of .01 (r = 0.699). Marketing mix was significantly related to tourist revisit behavior at a level of .01 (r = 0.597). In addition, image perception and marketing mix significantly affected tourist revisit behavior at a level of .01. The predictive power was 50.2%.